Studi of factors that affect enzyme activity in Avocado fruit (Persea americana) - Reynaldi, Muhammad Andre; Erwansani, Enggy; Yuswar, Muhammad Akib; Najini, Robby (Universitas Tanjungpura, 2025)
Avocado contains lipase enzyme. Enzymes can be found in avocado seeds. Factors that can affect Alanin Transaminase (ALT) enzyme activity are temperature increase, pH, substrate concentration, enzyme concentration, inhibitors and storage time. The study aims to investigate the effect of various factors of temperature, pH, and substrate concentration on enzyme activity. Research on factors that affect enzyme activity in avocado fruit was carried out by enzyme preparation in 3 stages of testing the effect of temperature, pH, and substrate concentration. The results of observations made in testing several factors. Observations show that temperature has a significant effect on changes in color and viscosity of the sample. Avocado is a source of various enzymes such as lipase, polyphenol oxidase, and peroxidase. These enzymes play an important role in various biochemical reactions in fruit. Research conducted shows that enzymes in avocado have a role as biocatalysts that can accelerate chemical reactions.